Exploring the efficacy of in-vitro low-temperature plasma treatment on single and multispecies dental cariogenic biofilms - Figueira, Leandro Wagner [UNESP]; Panariello, Beatriz; Koga-Ito, Cristiane Y. [UNESP]; Duarte, Simone (Springer Nature, 2024)
The primary aim of this study was to investigate the impact of treatment with low-temperature plasma (LTP) for varying exposure durations on a multispecies cariogenic biofilm comprising C. albicans, L. casei, and S. mutans, as well as on single-species biofilms of L. casei and C. albicans, cultured on hydroxyapatite discs. Biofilms were treated with LTP-argon at a 10 mm distance for 30 s, 60 s, and 120 s. Chlorhexidine solution (0.12%) and NaCl (0.89%) were used as positive (PC) and negative controls (NC), respectively. Argon flow only was also used as gas flow control (F). Colony-forming units (CFU) recovery and confocal laser scanning microscopy (CLSM) were used to analyze biofilm viability. LTP starting at 30 s of application significantly reduced the viability of multispecies biofilms by more than 2 log10 in all treated samples (p < 0.0001). For single-species biofilms, L. casei showed a significant reduction compared to PC and NC of over 1 log10 at all exposure times (p < 0.0001). In the case of C. albicans biofilms, LTP treatment compared to PC and NC resulted in a significant decrease in bacterial counts when applied for 60 and 120 s (1.55 and 1.90 log10 CFU/mL, respectively) (p < 0.0001). A significant effect (p ≤ 0.05) of LTP in single-species biofilms was observed to start at 60 s of LTP application compared to F, suggesting a time-dependent effect of LTP for the single-species biofilms of C. albicans and L. casei. LTP is a potential mechanism in treating dental caries by being an effective anti-biofilm therapy of both single and multispecies cariogenic biofilms.
Keywords: Antibacterial; Dental caries; Low-temperature plasma; Oral biofilms